Inhibition of mammalian nicotinic acetylcholine receptors by philanthotoxin analogues is strongly influenced by subunit composition - Kachel, Hamid Saeid (2015)
Philanthotoxin-433 (PhTX-433) is an active component of the Egyptian solitary digger wasp, Philanthus triangulum, venom which non-selectively inhibits several excitatory ion channels. With the aim of improving potency and selectivity, several synthetic analogues were developed based on the single or multiple modifications in the hydrophilic polyamine tail and hydrophobic aromatic head group of the PhTX. In the first part of this study, we investigated the pharmacological actions of two synthetic analogues, Philanthotoxin-343 (PhTX-343) and Philanthotoxin-12 (PhTX-12), on mammalian hetero- and homooligomeric nicotinic acetylcholine receptor (nAChR) subunit combinations expressed in Xenopus oocytes. Whole-cell currents in response to application of acetylcholine alone or co-applied with PhTX-analogue were studied electrophysiologically using two-electrode voltage-clamp at three different membrane holding potentials (VH = -60 mV, -80 mV and -100 mV). Concentration-inhibition curves were constructed and IC50 values estimated for each holding potential. The IC50 (95% CI, n=oocytes) values for PhTX-343 inhibition of α3β4, α3β2, α4β2, α4β4, α7, α3β4(F255V), α4β2(V253F) and α1β1δγ peak currents at -100 mV were 0.07 µМ (0.05-0.10 µМ, n=9), 3.20 µМ (1.69-6.26 µМ, n=8), 0.14 µМ (0.09-0.21 µМ, n=7), 0.28 µМ (0.17-0.46 µМ, n=6), 8.7 µМ (6.9-11.0 µМ, n =9), 0.01 µМ (0.01-0.02 µМ, n=8), 0.10 µМ (0.06-0.16 µМ, n=8) and 3.2 µМ (2.5-4.1 µМ, n=9) respectively; for PhTX-12 they were 2.03 µМ (1.22-3.26 µМ, n=8), 74.0 µМ (21-259 µМ, n=10), 1.6 µМ (0.7-3.6 µМ, n=11), 1.82 µМ (0.81-4.11 µМ, n=9), 12.1 µМ (9.0-16.0 µМ, n =10), 1.0 µМ (0.5-2.0 µМ, n=5), 3.4 µМ (1.3-8.7 µМ, n=9) and 5.0 µМ (2.8-8.8 µМ, n=8) respectively; i.e. in contrast to M-nAChR, PhTX-343 was more potent than PhTX-12 in all cases. All IC50s were lower when inhibition was measured after 1 minute of application indicating use dependence. For inhibition of heteromeric nAChRs, the peak potency of PhTX-343 was strongly augmented by holding the cell at more negative VH while this was not the case for PhTX-12 where only weak voltage-dependence was observed. The inhibition of homomeric α7 receptors by PhTX-343 was voltage-independent, whereas the block by PhTX-12 was voltage-dependent. In addition, these two synthetic analogues were different in their recovery rates (PhTX-12 was generally faster than PhTX-343) but they were similar in their mechanism of action, non-competitive inhibition. In the second part of the project, I explored the structure-activity relations of twenty one synthetic analogues, with a view to improving their activity and selectivity on rat neuronal α4β2 and α3β4 nAChRs at VH = -100 mV. We showed that the presence of positive charge in the polyamine tail of PhTX compounds is essential for nAChR subtype selectivity and its removal made the molecule lose its selectivity. Also, it appears that adding a bulky group to the terminal ammonium drastically reduced activity whereas a similar addition to the head region it increased their potency. In addition, we identified the key regions and substitutions responsible for increasing PhTX activity, cyclohexylalanine in place of tyrosine, and selectivity, phenyl group. Analogues having cyclohexylalanine and a phenolic group in the head region showed IC50 values in the low nano-molar and pico-molar (160-400 pM) range. These data suggest that PhTXs could serve as lead compounds for highly potent and selective inhibitors of N-nAChRs.